The Nigeria national health insurance authority act and its implications towards achieving universal health coverage - Ipinnimo, Tope; Durowade, Kabir; Afolayan, Christiana; Ajayi, Paul; Akande, Tanimola (The Nigerian postgraduate medical journal, 2022)
The National Health Insurance Scheme (NHIS) faced several inherent and systemic drawbacks towards achieving universal health coverage for all Nigerians, and this has led to the signing of the new National Health Insurance Authority Act (NHIA), 2022. This article highlights the benefits of NHIA, discusses the possible challenges and the way forward in its implementation. A narrative review of past literature searched in PubMed, MEDLINE, African Journal Online, and Goggle was conducted. A total of 76 publications were initially retrieved and following data triangulation, 55 were finally used. The authors also included their experiences. The NHIA addressed some of the shortcomings of the previous NHIS, however, it would still face several challenges in its implementation such as low government funding priority to health, shortage of healthcare workers and poor healthcare coverage, as well as problems with enforcement as it mandates all Nigerians to enroll. These and other impending constraints must be surmounted and all stakeholders must be involved to ensure the Act accomplishes its aim.